Electronic cigarettes: Ally or an enemy in combating tobacco-use-associated diseases - An integrative review - Hunny Sharma; Manisha Ruikar (Wolters Kluwer Medknow Publications, 2023)
Introduction: E-cigarettes (ECs) portable battery-operated devices developed as a strategy for tackling tobacco-related harm are now becoming a global threat to human health. Objectives: This integrative review aims to throw some light on the effect of ECs on human health and determine the safety of ECs with or without nicotine with long-term usage. Methods: This integrative review includes findings from Randomized and non-randomized clinical trials, and laboratory-based Human studies; published in the English language in the last four years. Literature search sources were online databases such as PubMed, Medline, EMBASE, Web of Science, Google Scholar. Results: Following systematic search using inclusion and exclusion criteria, 21 articles were included in the final review. ECs result in an acute increase in cardiac Sympathetic Nerve Activity (SNA), pronounced as Electrocardiogram (ECG) changes resulting in a greater risk of sudden death for those with co-morbidities. ECs with or without nicotine can adversely affect lung function and can precipitate obstructive pulmonary diseases. ECs may also adversely affect oral health due to increased bacterial pathogenicity and periodontitis. At last, these nicotine-containing ECs can yield nicotine comparable to Traditional cigarettes (TCs) and sometimes to a much greater extent, thus posing the threat of the user becoming nicotine dependent. Conclusion: Although ECs are less harmful than TCs in combustible inhaled constituents, their long-term safety can still not be ascertained due to the scarcity of long-term studies and conflicting results.